Development of HVAC Virtual Laboratory (HV-LAB version 1.0) / Mohd Faez Zainol, Ts. Shikh Ismail Fairus Shikh Zakaria and Dr. Muhammad Zulkarnain - Zainol, Mohd Faez; Shikh Zakaria, Shikh Ismail Fairus; Zulkarnain, Muhammad (2021)
Laboratory-based assessment is one of the crucial assessments in the institution of higher learning especially the engineering technology programme. Simulated laboratories are changing the nature of laboratory activities, and there is a long-running debate about the value of hands-on versus simulated laboratories. Hands-on advocates emphasise design skills, while simulated laboratories advocates focus on conceptual understanding. Interest in simulated laboratories versus hands-on has increased based on two factors: advancement in technology and cost pressure. Educational goals of hands-on laboratories activities focus on conceptual understanding, professional skills, design skills and social skills, but not all the equipment provide professional skill to the students. Most equipment are designed and built to explain the conceptual understanding only. Due to this, this paper presents the Development of HVAC Virtual Laboratory (HV-Lab); Recirculation Air Conditioning System Training Unit (RACSTU) using MATLAB/Simulink. RACSTU is located at the Fundamental HVAC Laboratories, Department of Mechanical Engineering Technology, Universiti Teknikal Malaysia Melaka (UTeM). The HV-Lab system was designed as the laboratory experimental setup. General equations were defined separately for each state of air property in RACSTU then experiments were conducted based on fifteen (15) different cases. Using these equations and experimental data MATLAB/Simulink models for every state of air property were created. The MATLAB/Simulink models were combined and verified with experimental results. The simulation results show that the experimental results are compatible with the experimental results for each state.